2022
DOI: 10.1177/00224278221081140
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Head Injury as an Acquired Neuropsychological Risk Factor for Adolescent Delinquency

Abstract: Objectives This study aims to parse out the effects of childhood head injury (HI) as an acquired neuropsychological deficit that impacts adolescent delinquent behavior, while accounting for other early-life risk factors and potential temporal ordering. Methods Nationally representative prospective data from the UK Millennium Cohort Study (MCS; N = 13,287) and a series of logistic and binomial regressions are used to examine the relationship between early-life risk factors, HI, and adolescent delinquent behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…The current study aimed to examine the common and unique associations between head injury and antisocial personality features in adolescence among a sample of juvenile justice involved youth. While existing evidence suggests that head injury is associated with general delinquency (Connolly & McCormick, 2019; Mongilio, 2022) and aggressive offending (Schwartz, 2021), less is known about whether head injury is related to other symptoms robustly correlated with future ASPD, such as failure to conform to social norms, deceitfulness, failure to plan, a reckless disregard for others, irresponsibility, and lack of remorse. As assessment of these characteristics are commonly used in many juvenile justice youth assessment instruments and argued to be predictive of future problematic behavior and offending (Skodol & Oldham, 2021; Livanou et al, 2019), thus a better understanding of the underlying factors associated with these problems could help create more targeted prevention and intervention programming.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The current study aimed to examine the common and unique associations between head injury and antisocial personality features in adolescence among a sample of juvenile justice involved youth. While existing evidence suggests that head injury is associated with general delinquency (Connolly & McCormick, 2019; Mongilio, 2022) and aggressive offending (Schwartz, 2021), less is known about whether head injury is related to other symptoms robustly correlated with future ASPD, such as failure to conform to social norms, deceitfulness, failure to plan, a reckless disregard for others, irresponsibility, and lack of remorse. As assessment of these characteristics are commonly used in many juvenile justice youth assessment instruments and argued to be predictive of future problematic behavior and offending (Skodol & Oldham, 2021; Livanou et al, 2019), thus a better understanding of the underlying factors associated with these problems could help create more targeted prevention and intervention programming.…”
Section: Discussionmentioning
confidence: 99%
“…According to the American Psychological Association, antisocial personality features manifests in "repeated violations of the law, exploitation of others, deceitfulness, impulsivity, aggressiveness, reckless disregard for the safety of self and others, and irresponsibility, accompanied by lack of guilt, remorse, and empathy" (APA, 2020). Head injuries may have adverse effects on the development of self-control, which is related to a range of antisocial behaviors (Mongilio, 2022;Schwartz et al, 2017) and externalizing as well as internalizing problems (Connolly & McCormick, 2019;McCormick et al, 2021). As one study concluded, "head injury may play a significant role in blunting the decline in impulsivity across development, exposing an additional risk factor for antisocial behavior" (Fullerton et al, 2019(Fullerton et al, , p. 1035).…”
Section: Head Injuries and Antisocial Personality Features In Adolesc...mentioning
confidence: 99%
See 2 more Smart Citations
“…The consequences of both conduct problems and head injuries are well known and include increased likelihood of delinquency and criminal behavior (Kennedy et al, 2017;Mongilio, 2022). A better understanding of how their pathways link during development is therefore important for intervention and prevention practices aimed at jointly reducing both.…”
Section: Introductionmentioning
confidence: 99%